Association of Social Frailty With Both Cognitive and Physical Deficits Among Older People - Tsutsumimoto, Kota; Doi, Takehiko; Makizako, Hyuma; Hotta, Ryo; Nakakubo, Sho; Makino, Keitaro; Suzuki, Takao; Shimada, Hiroyuki (Journal of the American Medical Directors Association, 2017)
Our objective was to investigate the association between social frailty and cognitive and physical function among older adults. This was a cross-sectional study. We examined community-dwelling adults in Japan. Participants comprised 4425 older Japanese people from the National Center for Geriatrics and Gerontology-Study of Geriatric Syndromes. Social frailty was defined by using responses to 5 questions (going out less frequently, rarely visiting friends, feeling unhelpful to friends or family, living alone, and not talking with someone every day). Participants showing none of these components were considered nonfrail; those showing 1 component were considered prefrail; and those showing 2 or more components were considered frail. To screen for cognitive deficits, we assessed memory, attention, executive function, and processing speed. Having 2 or more tests with age-adjusted scores of at least 1.5 standard deviations below the reference threshold was sufficient to be characterized as cognitively deficient. To screen for physical function deficits, we assessed walking speed (<1.0 m/s cut-off) and grip strength (<26 kg for men; <18 kg for women cut-off). Scoring below the cut-off point on 1 or more tests was sufficient to be characterized as physically deficient. The prevalence of social frailty was the following: nonfrailty, 64.1% (N = 2835); social prefrailty, 24.8% (N = 1097); social frailty, 11.1% (N = 493; P for trend < .001). All cognitive function tests (word list memory, Trail Making Test parts A and B, and the symbol digit-substitution task) significantly varied between social frailty groups; physical function (gait speed and grip strength) also varied between social frailty groups (all Ps for trend <.001). Referred to social nonfrailty, social frailty was independently associated with each cognitive deficit (odds ratio = 1.61, 95% confidence interval 1.13-2.30) and deficits in physical function (odds ratio = 1.99, 95% confidence interval 1.57-2.52) after adjusting for covariates. This study revealed that social frailty is associated with both cognitive and physical function among Japanese older adults. And social frailty status was also negatively associated with physical function. Further studies are needed to elucidate if a casual association exists between social frailty and cognitive and physical function.